Improning the effektiness of legal education of foreign students - Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article is talking about the importance of law education and the methods and forms of work with foreigners students at the Law Institute of NAU. Attention is accentuated on the specifics of the lecturing of discipline «Jurisprudence» and «Basics of Law» for students from other countries, in several groups, and also on the peculiarities of law education for foreigners in Ukrainian groups.